2017
DOI: 10.1371/journal.pone.0179923
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of Deepwater Horizon impacts on the benthic infauna of the northern Gulf of Mexico continental slope

Abstract: The Deepwater Horizon oil spill occurred in spring and summer 2010 in the northern Gulf of Mexico. Research cruises in 2010 (approximately 2–3 months after the well had been capped), 2011, and 2014 were conducted to determine the initial and subsequent effects of the oil spill on deep-sea soft-bottom infauna. A total of 34 stations were sampled from two zones: 20 stations in the “impact” zone versus 14 stations in the “non-impact” zone. Chemical contaminants were significantly different between the two zones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Generally, tardigrades are not a dominant component of the meiofauna and the abundance of marine tardigrade taxa is typically low within samples (Jørgensen et al 2010;Fontoura et al 2017). In the Gulf of Mexico deep-sea, Tardigrada is also consistently reported as a minor contributor to meiofaunal community composition (Baguley et al 2006;Landers et al 2012;Reuscher et al 2017;Cisterna-Céliz et al 2019). Additionally, Romano et al (2011) reported a low average abundance of tardigrades per positive sample (1.5 specimens/100 cm 3 sample).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, tardigrades are not a dominant component of the meiofauna and the abundance of marine tardigrade taxa is typically low within samples (Jørgensen et al 2010;Fontoura et al 2017). In the Gulf of Mexico deep-sea, Tardigrada is also consistently reported as a minor contributor to meiofaunal community composition (Baguley et al 2006;Landers et al 2012;Reuscher et al 2017;Cisterna-Céliz et al 2019). Additionally, Romano et al (2011) reported a low average abundance of tardigrades per positive sample (1.5 specimens/100 cm 3 sample).…”
Section: Discussionmentioning
confidence: 99%
“…While several deep-sea studies in this region have included Tardigrada in phylum level compositional analyses of meiofaunal communities (e.g. Baguley et al 2006;Landers et al 2012;Reuscher et al 2017;Cisterna-Céliz et al 2019), these did not include identifications at lower taxonomic levels. Thus far, only 15 tardigrade taxa have been recorded from the Gulf of Mexico (Romano 2009 and references therein;Romano et al 2011;Santos et al 2019).…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%
“…In 2011, meiofaunal richness was lower (28.5%) in the impacted (10 taxa/sample) areas than the surrounding reference (14 taxa/sample) areas (Montagna et al, 2017a). As of 2014, meiofaunal taxa richness remained lower in the impacted areas (7.6 taxa/sample) versus the reference areas, suggesting that a full recovery had not occurred as of 4 years after the DWH (Reuscher et al, 2017).…”
Section: Meiofaunamentioning
confidence: 96%
“…For meiofauna, data from the Northern Gulf of Mexico Continental Slope Study (NGOMCSS, Pequengnat et al, 1990), the Deep Gulf of Mexico Benthos Program (DGoMB; Baguley et al, 2006;Rowe and Kennicutt, 2009), and post-DWH, the NRDA (Montagna et al, 2013;Reuscher et al, 2017) were combined to create a long-term (decadal) time series ( Supplementary Figure 3 and Supplementary Table 3). Shannon diversity has decreased and the nematode:copepod ratio has increased continuously in the nGoM since the 1980's, which were consistent with a long-term decreasing ecological quality status (EQS) unrelated to DWH.…”
Section: Meiofaunamentioning
confidence: 99%
“…One year after the spill the hydrocarbon contamination and damage to the benthic fauna persisted, but signs of a mild recovery were detected [12,19]. Four years after the spill there were indicators that meiofauna had recovered some, as the nematode to copepod ratio had decreased to background levels [20], but taxonomic richness was still significantly lower in the affected areas indicating no recovery from the primary damaging effects. Macrofauna still suffered from significantly lower diversity and taxa richness in 2014 [20].…”
Section: Introductionmentioning
confidence: 99%